2000
DOI: 10.1007/s004670000385
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids and nephron mass control

Abstract: Advances in the molecular biology of retinoids have provided evidence that vitamin A profoundly influences the differentiation of the whole embryo. In addition to its well-characterized role in primary body axis and central nervous system formation, vitamin A is also required for the ad hoc development of numerous tissues and organs, including the kidney. This review will focus on the emerging evidence that the development of the urogenital tract depends on retinoids. In order to understand the role of vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 50 publications
1
31
0
1
Order By: Relevance
“…Moreover, it has been shown that vitamin A deficiency causes renal anomalies in mice and potentially regulates the expression of HOX genes [16], suggesting that potential environment-gene interaction could produce a similar phenotype, as a result of dietary deficiency, without both copies of both genes having to be deleted.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that vitamin A deficiency causes renal anomalies in mice and potentially regulates the expression of HOX genes [16], suggesting that potential environment-gene interaction could produce a similar phenotype, as a result of dietary deficiency, without both copies of both genes having to be deleted.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more and more scientists believe that congenital nephron deficit could be a 'missing link' in understanding of the etiology of essential hypertension. 131 For many years, data on fetal renal function have been insufficient and indirect. Investigations were carried out mainly in experimental animals and aborted fetuses.…”
Section: Fetal Urinary Systemmentioning
confidence: 99%
“…Since the lack of nephrons after birth is unrecoverable, numerous studies have been conducted to detect factors that in some way may impair the process of nephrogenesis. 131 Studies conducted on the cell cultures of the fetal kidney showed that retinoids, metabolites of vitamin A, have a significant impact on the number of nephrons and that this effect is dose-dependent. Vitamin A deficiency in pregnant women is rare in developed countries but is more frequently observed in underdeveloped countries as a result of insufficient food intake.…”
Section: Fetal Urinary Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinoic acid (RA), 13-cis retinoic acid (the active retinoid in the antiacne pharmaceutical Accutane), retinol (vitamin A, the primary dietary precursor of RA), and other retinoids including retinaldehydes like 11-cis retinal (the chromophore associated with rhodopsin) influence a broad range of physiological and pathological processes (reviewed by Pfahl and Chytil, 1996;Gilbert and Merlet-Benichou, 2000;Reifen, 2002;Maden, 2002;Biesalski and Nohr, 2003;Bonet et al, 2003;Wang, 2003). The physiological significance of retinoids was originally inferred from the relationship between dietary deprivation or excess intake of vitamin A and pathologies as diverse as hepatoxicity, carcinogenesis, psychosis, and blindness (reviewed by Underwood, 2004).…”
mentioning
confidence: 99%